Analysis of failure modes and effects in the installation of solar energy on residential roofs in Imperatriz/MA: an FMEA tool approach - Silva, Cayllon Victor Nascimento; Cavaignac, André Luís de Oliveira; Uchoa, Jhelison Gabriel Lima (Brazilian Journal of Production Engineering, 2020)
This work applies the FMEA tool in the installation of solar energy on residential roofs of Imperatriz/MA, through a case study. Considering the photographic records made, it was identified nonconformities in relation to Regulatory Standards 35, 6, 10 and 18 and also failures in the installation process. Three processes were defined for the application of FMEA tool. The results obtained demonstrate that the highest risk index involves an essential PPE, the helmet, not used by any of the workers in the study, that falling from a significant height can result in death. In addition to impacts, the helmet also protects against electric shock. It was also noted the possibility of falling down stairs and falling from the roof, as well as the total absence of fall safety devices. In this way, as final considerations, a corrective action plan is proposed for the failures of the analyzed solar energy installation processes, in order to ensure and certify the safety of workers directly involved in this area.